A catalyst for achieving deep desulfurization at below 80°C using O2 as an oxidant, a preparation method and application thereof
By using CeOx-MoOy/TS-1 composite material as a catalyst, deep desulfurization is achieved with oxygen as an oxidant below 80°C, and the problems of high oxidant cost, harsh catalyst preparation conditions and high reaction temperature in the prior art are solved, and a low-cost, environmentally friendly and efficient desulfurization effect is achieved.
Patent Information
- Application Number
- CN202310371903.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-10
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-04-10
AI Technical Summary
In the existing oxidation and desulfurization methods, the oxidant costs are high and unstable, the catalyst preparation conditions are harsh, the reaction temperature is high, the fuel quality is reduced, and it is difficult to achieve deep desulfurization below 80°C.
CeOx-MoOy/TS-1 (x=1.5~2, y=2~3) composite material was used as a catalyst, and deep desulfurization was achieved by a simple preparation process below 80°C using oxygen as an oxidant.
Deep desulfurization with oxygen as an oxidizing agent below 80°C is achieved. The catalyst has excellent reusability, is suitable for industrial production, is low in cost, and can effectively maintain the quality of oil.
Smart Images

Figure CN116159592B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the cross-field of nanocatalysis and environmental protection technology, and relates to a composite material, a preparation method and an application thereof for achieving deep desulfurization with O2 as an oxidant below 80°C, and provides a low-temperature oxidative desulfurization method based on CeOx-MoOy / TS-1 (x=1.5-2, y=2-3). Background Art
[0002] With the rapid development of industry, fuel oil is used more and more widely, but the sulfur oxides produced by the combustion of fuel oil bring many harms to human society, pollute the air environment, and seriously threaten human health. Countries around the world require that the sulfur content be reduced to below 10ppm.
[0003] The oxidative desulfurization scheme is low temperature, normal pressure, and mild reaction conditions, and is a green desulfurization method in the 21st century. At present, the commonly used oxidants in the oxidative desulfurization method are hydrogen peroxide and tert-butyl hydroperoxide, which not only have high reaction costs but are also unstable. Therefore, everyone chose green, safe, and cheap oxygen as the oxidant.
[0004] Oxygen is an inert gas and very stable, so it is very important to prepare a catalyst that can activate oxygen under mild conditions. In 2019, Yilin Dong et al. prepared CoMo bimetallic oxides using a coprecipitation method (Catal. Sci. Technol., 2019, 9, 2915), and the conversion rate of dibenzothiophene was 100% at 110°C. However, the problem is that the reaction temperature is too high, which will cause co-oxidation of other components in the fuel and reduce the quality of the fuel.
[0005] In 2019, Mingyue Chi et al. proposed a novel and efficient polyoxometalate (POM, Anderson-type Na3H6CrMo6O 24 ) and deep eutectic solvents (DESs) coupled biomimetic catalytic system (Applied Catalysis B: Environmental 259 (2019) 118089), the coupled system was applied to oxidative desulfurization, and showed excellent desulfurization performance at 60 ° C and normal pressure. Although catalysts such as polyoxometalates and ionic liquids can achieve deep desulfurization below 100 ° C, their catalyst preparation conditions are harsh and the raw materials are expensive, which is not conducive to industrial development.
[0006] In 2020, Yu Liu et al. prepared Co-Ni-Mo-O mixed metal oxide using a sacrificial template method (Industrial & Engineering Chemistry Research 2020 59(14), 6488-6496), which can completely oxidize DBT in 4 hours at 100°C and atmospheric pressure. This catalyst also causes co-oxidation of other components in the fuel at a reaction temperature of 100°C, reducing the quality of the fuel.
[0007] In 2020, Yanchen Wei et al. fixed 5,10,15,20-tetraphenylporphyrin manganese chloride (TPPMnCl) on hexagonal boron nitride (h-BN) (ACS Sustainable Chem. Eng. 2020, 8, 1015-1022) and added isobutyraldehyde sacrificial agent to achieve ultra-deep aerobic oxidation desulfurization of diesel at room temperature. Adding isobutyraldehyde to cheap metal catalysts can achieve oxygen oxidation desulfurization at room temperature, but this will not only make it difficult to separate it from the reaction liquid, but also greatly increase production costs. Therefore, the temperature must be below 100°C during the oxidation desulfurization process to ensure the quality of the oil, and the lower the reaction temperature, the more energy-saving and environmentally friendly it is. The mild reaction conditions and simple preparation process are more in line with the development needs of low energy consumption and high efficiency.
[0008] The catalyst of the present invention can realize oxygen oxidation desulfurization below 80°C, and the raw materials are cheap and the preparation process is simple. It is not only conducive to energy conservation and emission reduction, but also can be industrialized and developed in large quantities. Summary of the invention
[0009] In order to realize catalytic oxidation desulfurization under mild conditions using oxygen as an oxidant, the present invention provides a highly dispersed low-valent composite transition metal CeOx-MoOy / TS-1 (x=1.5~2, y=2~3). The prepared composite material is used as a heterogeneous catalyst to realize oxidation desulfurization using oxygen as an oxide, and has excellent reusability.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is:
[0011] A method for preparing a molybdenum-based catalyst for achieving deep desulfurization using O2 as an oxidant at below 80°C, comprising the following steps:
[0012] (1) Preparation of mixed solution
[0013] 1.1) Add cationic surfactant hexadecyltrimethylammonium bromide to pure water, heat to 20℃~60℃, stir at 400~1000rpm for 10-40min until the solution is evenly mixed, then add ammonia solution dropwise to the solution and continue stirring for 5-30min. Ammonia solution is added during the reaction to accelerate the hydrolysis rate of tetraethyl orthosilicate and tetrabutyl titanate.
[0014] 1.2) Continue to drop the mixed solution of ammonium heptamolybdate solution and cerium nitrate into the solution, and continue to stir for 10 to 60 minutes. During the reaction, the ammonium molybdate ions and the CTAB cations combine with each other due to electrostatic interaction, wherein the concentration of the ammonium heptamolybdate solution is 0.03 to 0.2 mol / L, and the concentration of the cerium nitrate is 0.03 to 0.2 mol / L.
[0015] 1.3) Tetraethyl orthosilicate is added thereto and stirring is continued for 30-120 minutes. During the reaction, tetraethyl orthosilicate is hydrolyzed into silica oligomers under the action of ammonia water. As time goes on, it is further hydrolyzed into Si-O bonds and then interwoven into a network.
[0016] 1.4) Finally, add 0.5-3.5 ml of tetrabutyl titanate and continue stirring for 1-6 hours to obtain a mixed solution. During this process, tetrabutyl titanate is hydrolyzed into Ti-O bonds and forms a titanium silicon molecular sieve together with Si-O, wrapping the active metal thereon.
[0017] (2) The reaction solution obtained in step (1) is centrifuged in a centrifuge, the obtained solid phase is washed with anhydrous ethanol and then centrifuged at a speed of 8000-10000 rpm for 2-5 times, the liquid phase is removed, and the obtained solid phase is dried at 80-100° C. for 10-12 hours.
[0018] (3) After the sample dried in step (2) is cooled to room temperature, it is ground into powder; in an air atmosphere, the temperature is raised to 500-700° C. in a tube furnace and then calcined for 4-6 hours at a heating rate of 2-5° C. / min; and a CeOx-MoO3 / TS-1 (x=1.5-2) composite material is obtained.
[0019] (4) The CeOx-MoO3 / TS-1 (x=1.5-2) obtained in step (3) is calcined in a H2 / N2 mixed atmosphere at 200-600°C in a tube furnace for 2-6 hours at a heating rate of 2-5°C / min to obtain a CeOx-MoOy / TS-1 (x=1.5-2, y=2-3) composite material.
[0020] Furthermore, in the step (1), 0.05 g to 0.15 g of hexadecyltrimethylammonium bromide, 0.02 to 6 mL of aqueous ammonia, 0.3 to 1.5 mL of a mixture of ammonium heptamolybdate solution and cerium nitrate, 0.5 to 3 mL of tetraethyl orthosilicate, and 0.5 to 3.5 mL of tetrabutyl titanate are added to every 30 mL of pure water.
[0021] The CeOx-MoOy / TS-1 (x=1.5~2, y=2~3) composite material obtained by the above preparation method has a spherical structure with a smooth surface, a catalyst size of about 66nm, a uniform and highly dispersed active metal distribution, and a metal size of about 12nm.
[0022] The CeOx-MoOy / TS-1 (x=1.5-2, y=2-3) composite material obtained by the above preparation method is applied to the oxidative desulfurization process in a simulated oil system with dibenzothiophene as the desulfurization object, and CeOx-MoOy / TS-1 (x=1.5-2, y=2-3) is used as an oxidative desulfurization catalyst to achieve deep desulfurization. In the simulated oil system, decalin is used as a solvent, dibenzothiophene is a sulfur-containing species, tetradecane is a gas phase internal standard, and oxygen is a desulfurization oxidant. The oxidative desulfurization process is carried out at 20°C to 80°C, the reaction time is 60 to 720 minutes, and the benzothiophene conversion rate can reach more than 92%, and the highest can reach 98.7%.
[0023] The innovation of the present invention is that the catalyst is a CeOx-MoOy / TS-1 (x=1.5-2, y=2-3) composite material with high oxygen vacancy concentration, a theoretical active metal loading of 2-6wt%, an oxygen vacancy content of 20-50%, and contains two metals, Mo and Ce, wherein Mo includes two valence states: Mo 4+ 、Mo 6+ , low-valent metal Mo accounts for 40-80% (atomic percentage) of all Mo, and Ce includes two valence states Ce 3+ 、Ce 4+ Low-valent metal Ce accounts for 20-60% (atomic percentage) of all Ce, and the Ce / Mo (1:1-1:10) is adjusted to obtain the best ratio. This catalyst has a better ability to adsorb and activate oxygen, and it can achieve deep desulfurization with O2 as an oxidant under mild conditions at 80°C.
[0024] Beneficial effects of the present invention:
[0025] (1) The CeOx-MoOy / TS-1 (x=1.5-2, y=2-3) of the present invention is a new catalyst in the field of oxidative desulfurization using oxygen as an oxidant, and has a simple preparation process and mild reaction conditions.
[0026] (2) The present invention uses oxygen as the oxidant in the oxidative desulfurization process, with mild reaction conditions and low cost. The desulfurization rate can reach 98.7% under the reaction conditions of 80°C and 12h. It also has excellent reusability and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 TEM image of CeOx-MoOy / TS-1 (x=1.5~2, y=2~3) material prepared in Example 1.
[0028] Figure 2 This is the SEM image of CeOx-MoOy / TS-1 (x=1.5~2, y=2~3) material prepared in Example 1.
[0029] Figure 3 This is a graph showing the reaction temperature results of the CeOx-MoOy / TS-1 (x=1.5~2, y=2~3) material prepared in Example 1.
[0030] Figure 4 This is a diagram showing the recycling results of the CeOx-MoOy / TS-1 (x=1.5~2, y=2~3) material prepared in Example 1. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with actual implementation cases. Of course, the present invention is not limited to the following specific implementation cases.
[0032] Implementation Case 1
[0033] Step 1: Prepare the mixed solution
[0034] Take 0.05g of hexadecyltrimethylammonium bromide in a 50mL flask, add 30mL of pure water, stir at 400rpm for 10min at 20℃, add 6ml of 25wt% ammonia water to the solution, continue stirring for 5min, drop 1.5mL of 0.05mol / L ammonium heptamolybdate solution and 1.2ml of 0.05mol / L cerium nitrate mixed solution into the reaction solution, stir well for 10min, add 0.5mL of tetraethyl orthosilicate dropwise, stir for 2h, add 1ml of tetrabutyl titanate to the solution, continue stirring for 3h to obtain a mixed solution.
[0035] In the second step, the mixed solution was transferred to a 10 mL centrifuge tube and centrifuged at 10,000 rpm. After centrifugation, the liquid phase was dumped and anhydrous ethanol was added to the remaining solid for washing. This washing process was repeated three times and the remaining solid was placed in a vacuum drying oven at 80°C and dried for 12 hours.
[0036] The third step is to grind the obtained solid and calcine it at 500°C in a tubular furnace for 6 hours. During this process, the heating rate of the tubular furnace is 3.5°C / min, and the air introduction rate is 40mL / min. The obtained composite material is MoO3 / TS-1.
[0037] In the fourth step, the obtained composite material is placed in a tubular furnace and reduced and calcined for 4 hours at 200°C by introducing H2 / N2 mixed standard gas. During this process, the heating rate of the tubular furnace is 3°C / min, and the H2 / N2 mixed standard gas is introduced at 30mL / min, and the composite material obtained is CeOx-MoOy / TS-1 (x=1.5~2, y=2~3).
[0038] Figure 1 This is the TEM image of the CeOx-MoOy / TS-1 (x=1.5~2, y=2~3) material prepared in Example 1. It can be seen that the CeOx-MoOy / TS-1 (x=1.5~2, y=2~3) catalyst has a regular morphology, uniform size, and a spherical morphology.
[0039] The prepared material was used as a catalyst for oxygen oxidation desulfurization. Dibenzothiophene was used as a sulfur-containing species to prepare a simulated oil of 500ppm dibenzothiophene. 30mg of the catalyst was placed in a 50mL double-necked flask, and a stirring bar and 20mL of 500ppm simulated oil were added in sequence. Then, the mixture was placed in an oil bath, oxygen was introduced at 80°C, condensed water was circulated, and the reaction was performed for 12h. After the reaction was completed, the double-necked flask was placed in a cold water bath to terminate the reaction, and the temperature of the double-necked flask was allowed to drop to room temperature. Then, 1.5ml of internal standard solution (1ml of n-tetradecane was diluted to 25ml with decahydronaphthalene as solvent, and this solution was used as an internal standard) was added to the reaction system, and the obtained reaction solution was diluted to 30ml, and then the reaction system was filtered, and the DBT content was detected by GC-FID. The conversion rate of dibenzothiophene was calculated to be 98.3%.
[0040] Implementation Case 2
[0041] The first step is to take 0.1g hexadecyltrimethylammonium bromide in a 50mL flask, add 30mL pure water, stir at 600rpm for 40min at 40℃, add 0.02ml 25wt% ammonia water to the solution, continue stirring for 20min, drop 1mL of 0.1mol / L ammonium heptamolybdate solution and 1ml of 0.1mol / L cerium nitrate mixed solution into the reaction solution. Stir well for 30min, add 2mL tetraethyl orthosilicate dropwise, stir for 1h, add 2ml tetrabutyl titanate to the solution, continue stirring for 4h, and obtain a mixed solution.
[0042] In the second step, the mixed solution was transferred to a 10 mL centrifuge tube and centrifuged at 10,000 rpm. After centrifugation, the liquid phase was dumped and anhydrous ethanol was added to the remaining solid for washing. This washing process was repeated three times and the remaining solid was placed in a vacuum drying oven at 90°C and dried for 10 hours.
[0043] In the third step, the obtained solid is then ground and calcined in a tubular furnace at 400°C for 4 hours. During this process, the heating rate of the tubular furnace is 3.5°C / min, and the air introduction rate is 40mL / min. The prepared composite material is MoO3 / TS-1.
[0044] In the fourth step, the composite material was finally placed in a tubular furnace at 600°C and introduced into a H2 / N2 mixed standard gas for reduction calcination for 6 hours. During this process, the heating rate of the tubular furnace was 3°C / min, and the H2 / N2 mixed standard gas was introduced at 30mL / min, and the composite material obtained was CeOx-MoOy / TS-1 (x=1.5~2, y=2~3).
[0045] The prepared material was used as a catalyst for oxygen oxidation desulfurization. Using dibenzothiophene as the sulfur-containing species, a simulated oil of 500ppm dibenzothiophene was prepared. 30mg of the catalyst was placed in a 50mL double-necked flask, and a stirring bar and 20mL of 500ppm simulated oil were added in sequence. Then it was placed in an 80℃ oil bath, oxygen was introduced, and the reaction was performed for 8h. After the reaction was completed, the double-necked flask was placed in a cold water bath to terminate the reaction, and the temperature of the double-necked flask was allowed to drop to room temperature. Then 1.5ml of internal standard solution (1ml of n-tetradecane was diluted to 25ml with decahydronaphthalene as solvent, and this solution was used as an internal standard) was added to the reaction system, and the obtained reaction solution was diluted to 30ml, and then the reaction system was filtered, and the DBT content was detected by GC-FID. The benzothiophene conversion rate was calculated to be 94.2%.
[0046] Implementation Case 3
[0047] The first step is to take 0.15g of hexadecyltrimethylammonium bromide in a 50mL flask, add 30mL of pure water, stir at 600rpm for 20min at 60℃, add 5ml of 25wt% ammonia water to the solution, continue stirring for 30min, drop 1.2mL of 0.2mol / L ammonium heptamolybdate solution and 1.5ml of 0.15mol / L cerium nitrate mixed solution into the reaction solution. Stir well for 60min, add 1.5mL of tetraethyl orthosilicate dropwise, stir for 30min, add 1.2ml of tetrabutyl titanate to the solution, continue stirring for 6h, and obtain a mixed solution.
[0048] In the second step, the mixed solution was transferred to a 10 mL centrifuge tube and centrifuged at 10,000 rpm. After centrifugation, the liquid phase was dumped and anhydrous ethanol was added to the remaining solid for washing. This washing process was repeated three times and the remaining solid was placed in a vacuum drying oven at 100°C for 8 hours.
[0049] In the third step, the obtained solid is then ground and calcined in a tubular furnace at 700°C for 4 hours. During this process, the heating rate of the tubular furnace is 3.5°C / min, and the air introduction rate is 40mL / min. The obtained composite material is MoO3 / TS-1.
[0050] In the fourth step, the composite material is finally placed in a 600°C tubular furnace and introduced into a H2 / N2 mixed standard gas for reduction calcination for 2 hours. During this process, the heating rate of the tubular furnace is 3°C / min, and the H2 / N2 mixed standard gas is introduced at 30mL / min, and the composite material obtained is CeOx-MoOy / TS-1 (x=1.5~2, y=2~3).
[0051] The prepared material was used as a catalyst for oxygen oxidation desulfurization. Dibenzothiophene was used as a sulfur-containing species to prepare a simulated oil of 500ppm dibenzothiophene. 30mg of the catalyst was placed in a 50mL double-necked flask, and a stirring bar and 20mL of 500ppm simulated oil were added in sequence. Then it was placed in an 80℃ oil bath, oxygen was introduced, and the reaction was carried out for 10h. After the reaction was completed, the double-necked flask was placed in a cold water bath to terminate the reaction, and the temperature of the double-necked flask was allowed to drop to room temperature. Then 1.5ml of internal standard solution (1ml of n-tetradecane was diluted to 25ml with decahydronaphthalene as solvent, and this solution was used as an internal standard) was added to the reaction system, and the obtained reaction solution was diluted to 30ml, and then the reaction system was filtered, and the DBT content was detected by GC-FID. It was calculated that the conversion rate of dibenzothiophene can reach 97.3%.
[0052] Implementation Case 4
[0053] Take 0.08g hexadecyltrimethylammonium bromide in a 50mL flask, add 30mL pure water, stir at 500rpm for 20min at 30℃, add 3ml 25wt% ammonia water to the solution, continue stirring for 15min, drop 1mL of 0.1mol / L ammonium heptamolybdate solution and 2ml of 0.2mol / L cerium nitrate mixed solution into the reaction solution. Stir thoroughly for 20min, add 1mL tetraethyl orthosilicate dropwise, stir for 30min, add 1ml tetrabutyl titanate to the solution, continue stirring for 2h, transfer the mixed solution to a 10mL centrifuge tube, and centrifuge at 10000rpm. During the centrifugation process, pour the liquid phase and add anhydrous ethanol to the remaining solid for washing. After repeating this washing process three times, place the remaining solid in a vacuum drying oven at 80℃ and dry it for 12h. The obtained solid was then ground and calcined in a 550°C tubular furnace for 6 hours. The heating rate of the tubular furnace was 3.5°C / min and the air introduction rate was 40mL / min. The obtained composite material was MoO3 / TS-1. The obtained composite material was then reduced and calcined in a tubular furnace at 600°C by introducing H2 / N2 mixed standard gas for 4.5 hours. The heating rate of the tubular furnace was 3°C / min and the H2 / N2 mixed standard gas was introduced at 30mL / min. The obtained composite material was CeOx-MoOy / TS-1 (x=1.5~2, y=2~3).
[0054] The prepared material was used as a catalyst for oxygen oxidation desulfurization. Dibenzothiophene was used as a sulfur-containing species to prepare a simulated oil of 500ppm dibenzothiophene. 30mg of the catalyst was placed in a 50mL double-necked flask, and a stirring bar and 20mL of 500ppm simulated oil were added in sequence. Then it was placed in an 80℃ oil bath, oxygen was introduced, and the reaction was carried out for 6h. After the reaction was completed, the double-necked flask was placed in a cold water bath to terminate the reaction, and the temperature of the double-necked flask was allowed to drop to room temperature. Then 1.5ml of internal standard solution (1ml of n-tetradecane was diluted to 25ml with decahydronaphthalene as solvent, and this solution was used as an internal standard) was added to the reaction system, and the obtained reaction solution was diluted to 30ml, and then the reaction system was filtered, and the DBT content was detected by GC-FID. It was calculated that the conversion rate of dibenzothiophene can reach 92.6%.
[0055] Implementation Case 5
[0056] The rest of the implementation process is consistent with Implementation Case 1, except that 1.5 mL of 0.05 mol / L ammonium heptamolybdate solution and 1.2 mL of 0.05 mol / L cerium nitrate mixed solution are added dropwise to the reaction solution, replacing the mixed solution with (Mo:Ce=1:1), and the oxidation desulfurization time is shortened from 12 h to 6 h. The conversion rate of dibenzothiophene obtained by the reaction can reach 92.7%.
[0057] Implementation Case 6
[0058] The rest of the implementation process is consistent with Implementation Case 1. The reaction solution after the reaction is transferred to a 10mL centrifuge tube and centrifuged at 10000rpm for 10min. After dumping the liquid phase, the solid phase is washed. Using ethanol as a detergent, 5mL of acetone is added to the remaining solid phase, and it is centrifuged after ultrasonication for 6min. Centrifuge at 10000rpm for 10min, and take the remaining solid phase after dumping the acetone washing liquid into an oven. After drying at 100°C for 1h, wait for it to cool to obtain a regenerated catalyst. According to Case 6, the regenerated catalyst is applied to low-temperature oxidative desulfurization, and the DBT conversion rate for the second reuse is 95%. After being reused 5 times, the DBT conversion rate can still be maintained at about 90%. It can be seen that acetone washing can maintain the excellent reusability of the catalyst. Figure 4 This is a diagram showing the results of reuse of CeOx-MoOy / TS-1 (x=1.5~2, y=2~3) catalyst in implementation case 6.
[0059] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a molybdenum-based catalyst for deep desulfurization at 80°C using O2 as an oxidant, characterized in that: The molybdenum-based catalyst is a CeOx-MoOy / TS-1 composite material, x=1.5-2, y=2-3, the composite material is a spherical structure with a smooth surface, the active metal is evenly distributed and highly dispersed, wherein the active metal includes Mo and Ce, and CeOx-MoOy / TS-1 can achieve deep desulfurization with oxygen as an oxidant under mild conditions of 80°C; the theoretical loading amount of the active metal is 2~6wt%, the oxygen vacancy content is 20~50%, the low-valent metal Mo atoms account for 40~80% of all Mo, and the low-valent metal Ce atoms account for 20~60% of all Ce; comprising the following steps: (1) Add cationic surfactant hexadecyltrimethylammonium bromide to pure water and heat to 20 o C ~ 60 o C, after stirring for 10 to 40 min, add ammonia solution dropwise to the solution and continue stirring for 5 to 30 min; continue to drop a mixed solution of ammonium heptamolybdate solution and cerium nitrate into the solution and continue stirring for 10 to 60 min; add tetraethyl orthosilicate thereto and continue stirring for 30 to 120 min; finally, add 0.5 to 3.5 mL of tetrabutyl titanate thereto and continue stirring for 1 to 6 h to obtain a mixed solution; (2) centrifuging the reaction solution obtained in step (1), washing the obtained solid phase with anhydrous ethanol and centrifuging it for multiple times, removing the liquid phase, and drying the obtained solid phase; (3) After cooling the sample dried in step (2) to room temperature, grinding it into powder; heating it to 500-700°C in a tube furnace in an air atmosphere and calcining it for 4-6 h to obtain a CeOx-MoO3 / TS-1 composite material; (4) The CeOx-MoO3 / TS-1 obtained in step (3) is calcined in a tube furnace at 200-600°C for 2-6 hours in a H2 / N2 mixed atmosphere to obtain a CeOx-MoOy / TS-1 composite material.
2. The preparation method according to claim 1, characterized in that: In the step (1), 0.05 g to 0.15 g of hexadecyltrimethylammonium bromide, 0.02 to 6 mL of aqueous ammonia, 0.3 to 1.5 mL of a mixture of ammonium heptamolybdate solution and cerium nitrate, 0.5 to 3 mL of tetraethyl orthosilicate, and 0.5 to 3.5 mL of tetrabutyl titanate are added to every 30 mL of pure water.
3. The preparation method according to claim 1, characterized in that: In the step (1), the concentration of the ammonium heptamolybdate solution is 0.03-0.2 mol / L, and the concentration of the cerium nitrate is 0.03-0.2 mol / L.
4. An application of a molybdenum-based catalyst prepared by the preparation method according to claim 1, characterized in that: The CeOx-MoOy / TS-1 composite material obtained by the above preparation method is applied to the oxidative desulfurization process in a simulated oil system with dibenzothiophene as the desulfurization object. Using CeOx-MoOy / TS-1 as an oxidative desulfurization catalyst can achieve deep desulfurization.
5. The use according to claim 4, characterized in that: In the simulated oil system, decahydronaphthalene is used as solvent, dibenzothiophene is used as sulfur-containing species, tetradecane is used as gas phase internal standard, oxygen is used as desulfurization oxidant, and the oxidative desulfurization process is carried out at 80 o C, the reaction time is 360 ~720 min, and the benzothiophene conversion rate can reach more than 92%.
Citation Information
Patent Citations
Metal organic iron coordination compound, polyacid and titanium-silicon molecular sieve composite catalyst and preparation method thereof
CN111135867A
Cited By
Catalyst for low-temperature oxygen oxidation desulfurization of fuel oil and preparation method thereof
CN118022722A